Regional Economic Outlook, October 2019, Sub-Saharan Africa. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2019)
Regional Economic Outlook, October 2019, Sub-Saharan Africa.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet